KAJIAN EPISTEMOLOGI FILSAFAT ILMU TERHADAP ARTIFICIAL INTELLIGENCE SEBAGAI SUMBER PENGETAHUAN - Mahfuzha Pane; Daulat Saragi; Yacobus Ndona (STKIP Subang, 2026)
ABSTRACT The epistemological study of the philosophy of science regarding Artificial Intelligence (AI) as a source of knowledge has become important as technological developments influence the way knowledge is produced and validated in contemporary scientific practice. The main problem in this study is the epistemological position of artificial intelligence as a source of knowledge and the shifts in the concept of truth that it causes. This study aims to analyze the position of artificial intelligence as a source of knowledge from the perspective of the epistemology of the philosophy of science and identify epistemological shifts in the digital era. This study uses a qualitative approach with library research and a philosophical approach that focuses on epistemological analysis. Data were obtained from various relevant scientific literature and analyzed using descriptive-interpretive and critical-reflective techniques. The results show that artificial intelligence has a position as an entity involved in the process of knowledge production, but cannot be categorized as a legitimate source of knowledge as a whole because it lacks awareness, understanding of meaning, and reflective ability in the process of justifying truth. In addition, the development of artificial intelligence has given rise to an epistemological shift from knowledge based on causal explanations to knowledge based on predictions and operational effectiveness, which has resulted in changes in the criteria of truth and the emergence of epistemological problems such as justification crises, data bias, and algorithmic opacity.